ANALYSIS OF REGENCY READINESS LEVEL IN IMPLEMENTING AUTONOMY OF MINERAL RESOURCES MANAGEMENT IN WEST PAPUA PROVINCE - Juanita R. Horman; Aryo P. Wibowo (Puslitbang tekMIRA, 2013)
Reformation in Indonesia has resulted in a new policy, which is widely known as regional autonomy. In imple- menting this decentralisation concept, provinces, regencies and cities as governmental units are being given huge authorities and wider opportunities in terms of managing and developing their areas. This policy, however, could not be interpreted that the central government is transferring an absolute authority. It has to be viewed and be functioned properly as an instrument to accelerate regional developments and to contribute comprehensively to national development as well. In West Papua, natural resources management including mining sector has been a crucial part affecting the implementation of decentralisation. Managerial aspects that consist of planning, organising, monitoring and evaluating seem to be more complicated in practical actions. Therefore, a question usually appearing to be answered is that has West Papua been prepared and capable to face this policy with considering that this long-term policy might have numerous external and internal factors constraining its success. To determine the level of regional capability in facing mining sector autonomy, data regarding mining resources, human resources and regional income of mining activities had been collected from four samples of regencies, namely Fak-Fak, Sorong, Raja Ampat and Teluk Bintuni. These date were then evaluated using factor analysis to be rated and interpreted. The results show that the capability level of Teluk Bintuni is low. Sorong and Fak-Fak have medium levels, and Raja Ampat is in high level.